Diabetes Melitus Tipe 2 dengan Masalah Geriatri, Gangguan Elektrolit, dan Pneumonia pada Pasien Lansia - Inna Dwi Raisa; Maulina Debbyousha (Vitalitas Medis : Jurnal Kesehatan dan Kedokteran, 2026)
Diabetes mellitus type 2 is a chronic metabolic disorder that frequently affects elderly patients and is often accompanied by multiple comorbidities. The increasing prevalence of diabetes in the aging population contributes to higher morbidity and mortality, especially when complicated by geriatric syndromes, electrolyte imbalances, and infections such as pneumonia. This study aims to present a case of type 2 diabetes mellitus in an elderly patient with associated geriatric problems, electrolyte disturbances, and pneumonia. The method used is a descriptive case report based on clinical findings, laboratory examinations, and radiological assessment. A 76-year-old male presented with generalized weakness, weight loss, decreased appetite, respiratory symptoms, and functional decline. Physical examination and laboratory findings revealed uncontrolled diabetes, electrolyte imbalance, hypoalbuminemia, and signs of infection. Chest radiography confirmed pneumonia. Management included pharmacological therapy such as antibiotics, fluid and electrolyte correction, and supportive care, along with non-pharmacological interventions including dietary regulation and monitoring. The findings highlight the complexity of managing elderly patients with multiple comorbid conditions, emphasizing the need for a comprehensive and multidisciplinary approach. Early detection and appropriate management are essential to improve clinical outcomes and prevent further complications in geriatric patients with diabetes mellitus.